Avaliação da qualidade física, fisiológica e sanitária de sementes de milho durante o beneficiamento - Fessel, Simone Aparecida [UNESP]; Sader, Rubens; Paula, Rinaldo Cesar De [UNESP]; Galli, Juliana Altafin [UNESP] (Associação Brasileira de Tecnologia de Sementes, 2003)
The objective of this research was to evaluate the physical, physiological and sanitary quality of corn seeds during conditioning. Sixteen samples of a corn seed lot hybrid D766 produced in 2001/2002 was used, classified as medium short flat and short round, from the screens 20 and 22. The seed samples were obtained during the following conditioning steps: reception, pre-cleaning, post-gravity separator, post-grader and after bagging. The seeds were evaluated for the moisture content, standard germination, first germination count, speed of germination index, accelerated aging, cold test, electrical conductivity, seedling field emergence, health test through the filter paper and injury test. The experimental design used was completely randomized with 4 replications and the mean comparison was made through the Scott-Knott multiple path comparison test at 5% level of probability. According to the obtained results it was concluded that mechanical injury can occur at any stage of seed conditioning and is cumulative and the corn seed conditioning may improve the seed lot quality in for germination, vigor and health.

A pesquisa teve por objetivo avaliar a qualidade física, fisiológica e sanitária de sementes de milho durante as etapas de beneficiamento. Foram utilizadas 16 amostras de um lote de sementes do híbrido D766 safra 2001/2002 , classificado em sementes chatas médias curtas e redondas curtas, de peneiras 20 e 22. As amostras foram obtidas durante as fases do beneficiamento de recepção, pré-limpeza, pós-mesa de gravidade, pós-classificador e pós-ensaque. As sementes foram avaliadas quanto ao teor de água, germinação, primeira contagem da germinação, índice de velocidade de germinação, envelhecimento acelerado, teste de frio, condutividade elétrica, emergência das plântulas em campo, sanidade, através do teste de papel filtro e dano mecânico. Para análise estatística utilizou-se o delineamento inteiramente casualizado, com quatro repetições, e a comparação das médias foi feita usando-se o programa SAEG, teste de comparações múltiplas de Scott-Knott a 5% de probabilidade. Os resultados deste trabalho sugeriram que os danos mecânicos podem ocorrer em cada fase do processamento e são cumulativos e o beneficiamento de sementes de milho pode aprimorar a qualidade de sementes de um lote em termos de germinação, vigor e sanidade.
Quality evaluation of corn seeds during conditioning
Keywords: Zea mays L; germination; vigor; processing; mechanical injury; Zea mays L; germinação; vigor; processamento; injúria mecânica